Self Reported Risks Associated in Veterinary Profession (Indian Journal of Extension Education, 2017)
The present study was conducted in Uttar Pradesh and Maharashtra. Two hundred and six veterinarians comprising 82 Livestock Development Officers (LDOs) from state department, Maharashtra and 124 scientists from two animal science institutes were selected following the proportionate random sampling to understand the self reported risks in veterinary profession. Final data were collected personally through the two different interview schedule developed based on their nature of work. The severity of risks associated in the veterinary profession were identified and responses were taken on a three point continuum viz. less risky, moderately risky and highly risky separately for each event. Various activities were identified respondents were asked to mention their responses on a three point continuum based on the perceived severity of risk viz. least, moderate and severe. Frequencies and percentages were calculated for each risk reported by LDO’s and the scientists separately. Study revealed that field veterinarian and scientists perceived zoonoses, back pain and injuries and accidents as the top three extremely risky aspects of the veterinary profession. Veterinarians working in field felt animal assaults, spondylitis and exhaustion while the scientists perceived injuries, back pain, chemical hazards and exhaustion as the other the high risk associated in veterinary profession.